HUBUNGAN INTENSITAS NYERI PUNGGUNG BAWAH UNILATERAL DENGAN DERAJAT OSTEOARTRITIS LUTUT KONTRALATERA - Edy Irwanto,* Dwi Pudjonarko,* Hermina Sukmaningtyas** (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION LOW BACK PAIN LBP IS ONE OF THE MOST COMMON AND RECURRING FORMS OF MUSCULOSKELETAL PAIN IN BACK INJURIES OR DISC DEGENERATIVE DISEASES THAT CAUSE CHRONIC LBP WILL INCREASE THE BURDEN ON THE KNEE JOINT THEREBY TRIGGERING OR EXACERBATING THE OCCURRENCE OF OSTEOARTHRITIS OA OF THE KNEE